(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The deposit guarantee system in Uzbekistan plays an important role in ensuring the country’s financial stability and increasing the population’s confidence in the banking system. This system is aimed at protecting deposits held in banks and aims to minimize the risk of depositors losing their funds. The deposit guarantee system is managed by the Central Bank of the Republic of Uzbekistan and the Depositors’ Guarantee Fund of the Republic of Uzbekistan. One of the main features of the system is the establishment of maximum amounts of guaranteed deposits, the launch of rapid compensation mechanisms in the event of banks experiencing financial problems, and the provision of guarantees to the population to ensure stability. Also, the reforms implemented in the banking and financial system of Uzbekistan in recent years are aimed at increasing the efficiency of the guarantee system. This article analyzes the specific aspects of the deposit guarantee system in Uzbekistan, its impact on the national financial system and development prospects. Also, practical recommendations for further improving the system based on foreign experience are developed.